Wideband Tuning of Impedance Matching for actual RF Networks using AQPSO - Yin Xin; Tan Yang Hong; Liao Jiwang (Institute of Advanced Engineering and Science, 2013)
An adaptive wideband impedance matching technique using a passive PI-network is presented in the paper on the basis of adaptive quantum particle swarm optimization algorithms (AQPSO), which avoiding the drawbacks of the standard particle swarm optimization (PSO) algorithm. The Wideband Tuning technique is for actual RF chips. So on-chip models for RF capacitors and inductors are considered. And the effects of the parasitic component loss in the PI-network are analyzed. Then the circuit is simplified according to the sensitivities of the elements. Therefore, the computational complexity is dramatically reduced. Finally, the AQPSO algorithm is adopted to maximize the power transmission efficiency. Simulation results show that the proposed tuning technique can achieve good accuracy of impedance matching and load power. The reflection coefficient and VSWR obtained are also satisfactory. Moreover, the proposed method can be useful for software defined radio systems using a single antenna for multiple mobile and wireless bands. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3504